Highly efficient and robust Au/MgCuCr2O4 catalyst for gas-phase oxidation of ethanol to acetaldehyde - Liu, Peng; Hensen, Emiel J M (Journal of the American Chemical Society, 2013)
Gold nanoparticles (AuNPs) supported on MgCuCr2O4-spinel are highly active and selective for the aerobic oxidation of ethanol to acetaldehyde (conversion 100%; yield ∼95%). The catalyst is stable for at least 500 h. The unprecedented catalytic performance is due to strong synergy between metallic AuNPs and surface Cu(+) species. X-ray photoelectron spectroscopy shows that Cu(+) is already formed during catalyst preparation and becomes more dominant at the surface during ethanol oxidation. These Cu(+) species are stabilized at the surface of the ternary MgCuCr2O4-spinel support. Further kinetic measurements indicate that the Cu(+) species act as sites for O2 activation.